The Effectiveness of Reciprocal Teaching Method on Students’ Reading Comprehension of Recount Text - Fanny Sihombing; Jenita Anjani Br. Sembiring; Junita Siahaan (Universitas Majalengka, 2026)
Reading comprehension remains one of the fundamental skills in English language learning; however, many junior high school students continue to experience difficulties in identifying main ideas, supporting details, vocabulary in context, and sequences of events in recount texts. Although Reciprocal Teaching has been widely recognized as an effective instructional strategy, limited studies have specifically examined its effectiveness in teaching recount texts among eighth-grade students in Indonesian junior high schools using a quasi-experimental design combined with effect size analysis. Therefore, this study aimed to investigate the effectiveness of the Reciprocal Teaching Method on students’ reading comprehension achievement of recount texts at SMP Swasta Santo Yoseph Medan. This study employed a quantitative approach using a quasi-experimental design with a non-equivalent control group design. The participants consisted of 60 eighth-grade students, including 30 students in the experimental class and 30 students in the control class. Data were collected through a 20-item multiple-choice reading comprehension test administered as both a pre-test and a post-test. The collected data were analyzed using descriptive statistics, normality and homogeneity tests, an Independent Samples t-test, and Cohen’s d effect size analysis. The findings revealed that the experimental class achieved a higher post-test mean score (79.00) than the control class (65.67). The Independent Samples t-test indicated a statistically significant difference between the two groups (p < .001). Furthermore, Cohen’s d value of 1.28 demonstrated a large practical effect of the treatment. These findings indicate that the Reciprocal Teaching Method is effective in improving students’ reading comprehension achievement of recount texts and may serve as an alternative instructional strategy for English teachers.